The Development of 4C Competencies Integration Lesson Plan (RPP), Literation, PPK and HOTS for Elementary Schools - Kartono Kartono (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
The purpose of this study was to produce RPP models that integrate 4C, literacy, PPK and HOTS capabilities, which have been validated. The method used was the development research method Borg & Gall, from the introduction, development, and testing stages. In the first year, it has produced high-grade elementary school Thematic RPP that integrate 21st century competency (4C), literacy skills, reinforced Character Education (PPK) and validated HOTS so that they are suitable to be used as RPP models to strengthen these abilities.